2012
DOI: 10.1007/s11295-012-0516-5
|View full text |Cite
|
Sign up to set email alerts
|

SNP markers trace familial linkages in a cloned population of Pinus taeda—prospects for genomic selection

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer-Verlag. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your work, please use the accepted author's version for posting to your own website or your institution's repository. You may further deposit the accepted author's version on a funder's repository at a funder's request, provided it is not made publicly available until 12 months after publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
41
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 44 publications
12
41
2
Order By: Relevance
“…Interestingly, the large drop in PA at age 10 and 15 years seems to coincide with a period of intense competitive exclusion between trees at this age, perhaps exacerbated by the relatively narrow tree spacing (2.5 × 2.5 m). The observed extent of PA for tree height was comparable with that reported in other studies using clonal eucalypts (Resende et al, 2012a) and 1-6-year tree height in loblolly pine (Resende et al, 2012b, c;Zapata-Valenzuela et al, 2012). More recently, Beaulieu et al (2014a) tested GS in a halfsib population of white spruce and reported PA for 22-year tree height that were similar to those described here.…”
Section: Accuracy Of Gs Prediction Through Timesupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, the large drop in PA at age 10 and 15 years seems to coincide with a period of intense competitive exclusion between trees at this age, perhaps exacerbated by the relatively narrow tree spacing (2.5 × 2.5 m). The observed extent of PA for tree height was comparable with that reported in other studies using clonal eucalypts (Resende et al, 2012a) and 1-6-year tree height in loblolly pine (Resende et al, 2012b, c;Zapata-Valenzuela et al, 2012). More recently, Beaulieu et al (2014a) tested GS in a halfsib population of white spruce and reported PA for 22-year tree height that were similar to those described here.…”
Section: Accuracy Of Gs Prediction Through Timesupporting
confidence: 90%
“…More recently, empirical studies have all produced promising results in regards to acceleration of the breeding cycle for three tree species; namely, eucalypts (Eucalyptus spp.) (Resende et al, 2012a), loblolly pine (Pinus taeda L.) (Zapata-Valenzuela et al, 2012;Resende et al, 2012b, c) and white spruce (Beaulieu et al, 2014a, b). This study represents a novel approach over the preceding studies through the application of the non-model GBS SNP discovery pipeline, in addition to high missing data ratio imputation methods to produce GS prediction models.…”
Section: Introductionmentioning
confidence: 99%
“…So far, empirical accuracy estimates in forest trees have been reported only for small breeding populations of Pinus taeda and Eucalyptus (Resende et al, 2012a, b;Zapata-Valenzuela et al, 2012). As expected from deterministic and simulation models (Grattapaglia and Resende, 2011;Iwata et al, 2011), the accuracy of GS models for wood and growth traits in these species was slightly higher than that reported in the present study.…”
Section: Predictive Ability and Accuracy Of Gs Modelscontrasting
confidence: 55%
“…These simulations indicated that high accuracy of GEBVs could be obtained with populations of small effective size and high LD with a reasonably limited number of markers, but these represented idealized conditions. Recent results from empirical studies in small breeding populations confirmed that quite a high accuracy of GEBVs could be obtained (Resende et al, 2012a, b;Zapata-Valenzuela et al, 2012). They also showed that this approach could help speed up breeding cycles and significantly increase gains per time unit.…”
Section: Introductionmentioning
confidence: 86%
“…Simulation studies Resende 2011, Iwata et al 2011;Denis and Bouvet 2013) have already demonstrated the potential of GS for forest trees in diverse breeding and genetic scenarios. These theoretical studies have been complemented by the first empirical studies in forest trees (Zapata-Valenzuela et al 2012;Zapata-Valenzuela et al 2013;Resende et al 2012a;Resende et al 2012b), which have yielded medium-to high-level accuracies, even with limited numbers of markers (less than 5,000 SNPs). However, these preliminary results must be interpreted with caution, as they relate to populations with small effective sizes and thus favorably high linkage disequilibrium levels.…”
Section: Genomics and Breedingmentioning
confidence: 99%